A Qualitative Study of Substance use during Pregnancy: Implications for Reproductive Healthcare in Western Kenya - Yotebieng, Kelly A. (Afr J Reprod Health, 2016)
Women who use alcohol and drugs are often in their childbearing years, creating a need for integrated substance abuse and reproductive health services. However, our understanding of the social context and drivers of substance use during pregnancy, particularly in developing countries, is limited and largely unaddressed in clinical care. Our qualitative research explored the reproductive health of women of childbearing age who inject drugs and its implications for healthcare in Kisumu, Kenya. We used in-depth, semi-structured qualitative interviews with 17 women who inject drugs to explore reproductive health topics including knowledge, practices, and clinical interactions related to substance use during pregnancy. All but one woman had a prior pregnancy and two were pregnant during our study. Alcohol and drug use was prevalent throughout pregnancy, often described as a coping mechanism for stress. Women received mixed advice from family and social contacts regarding alcohol use during pregnancy, leading to differing perceptions of its health effects. Healthcare providers infrequently screened women for alcohol or drug use. Our analysis highlights the need for culturally appropriate alcohol and drug screening and counseling to be included in integrated reproductive health services in western Kenya.